Comparison of CT perfusion summary maps to early diffusion-weighted images in suspected acute middle cerebral artery stroke - Benson, John; Payabvash, Seyedmehdi; Salazar, Pascal; Jagadeesan, Bharathi; Palmer, Christopher S.; Truwit, Charles L.; McKinney, Alexander M. (European journal of radiology, 2015)
To assess the accuracy and reliability of one vendor's (Vital Images, Toshiba Medical, Minnetonka, MN) automated CT perfusion (CTP) summary maps in identification and volume estimation of infarcted tissue in patients with acute middle cerebral artery (MCA) distribution infarcts. From 1085 CTP examinations over 5.5 years, 43 diffusion-weighted imaging (DWI)-positive patients were included who underwent both CTP and DWI <12h after symptom onset, with another 43 age-matched patients as controls (DWI-negative). Automated delay-corrected postprocessing software (DC-SVD) generated both infarct “core only” and “core+penumbra” CTP summary maps. Three reviewers independently tabulated Alberta Stroke Program Early CT scores (ASPECTS) of both CTP summary maps and coregistered DWI. Of 86 included patients, 36 had DWI infarct volumes ≤70ml, 7 had volumes >70ml, and 43 were negative; the automated CTP “core only” map correctly classified each as >70ml or ≤70ml, while the “core+penumbra” map misclassified 4 as >70ml. There were strong correlations between DWI volume with both summary map-based volumes: “core only” (r=0.93), and “core+penumbra” (r=0.77) (both p<0.0001). Agreement between ASPECTS scores of infarct core on DWI with summary maps was 0.65–0.74 for “core only” map, and 0.61–0.65 for “core+penumbra” (both p<0.0001). Using DWI-based ASPECTS scores as the standard, the accuracy of the CTP-based maps were 79.1–86.0% for the “core only” map, and 83.7–88.4% for “core+penumbra.” Automated CTP summary maps appear to be relatively accurate in both the detection of acute MCA distribution infarcts, and the discrimination of volumes using a 70ml threshold.